PROPAGATION-BASED CONSTRAINT SOLVER IN IMS - Blynov, I.O. (Journal of Information Technologies in Education (ITE), 2012)
Article compiling the main ideas of creating propagation-based constraint solver, theoretical basis of constraint programming and its implementation in IMS (Insertion Modeling System)